Cytotoxic activity of Androctonus australis hector venom and its toxic fractions on human lung cancer cell line - Béchohra, Louisa (J Venom Anim Toxins Incl Trop Dis, 2016)
BACKGROUND: Several studies have showed that animal venoms are a source of bioactive compounds that may inhibit the growth of cancer cells, which makes them useful agents for therapeutic applications. Recently, it was established that venom toxins from scorpions induced cytotoxic, antiproliferative and apoptogenic effects on cancer cells. Therefore, the present study aims to investigate the cytotoxic activity of Androctonus australis hector (Aah) scorpion venom and its toxic fractions (FtoxG-50 and F3) on NCI-H358 human lung cancer cells. METHODS: The cytotoxic and antiproliferative activities were estimated using MTT assay, lactate dehydrogenase release and clonogenic assays. Apoptosis was evaluated by Hoechst 33258 staining, DNA fragmentation assay and caspase-3 activity. Oxidative stress was analyzed by reactive oxygen species, nitric oxide, malondialdehyde and protein carbonyl levels along with assessment of antioxidant status. In addition, alteration of mitochondrial membrane potential was analyzed by JC1 fluorescent dye. RESULTS: The present findings showed that F3 fraction was more cytotoxic towards NCI-H358 lung cancer cells with an IC(50) of 27.05 ± 0.70 μg/mL than venom alone (396.60 ± 1.33 μg/mL) and its toxic fraction FtoxG-50 (45.86 ± 0.91 μg/mL). Nevertheless, F3 fraction was not cytotoxic at these concentrations on normal human lung fibroblast MRC-5 cells. Inhibition of NCI-H358 cell proliferation after F3 fraction exposure occurred mainly by apoptosis as evidenced by damaged nuclei, significant DNA fragmentation level and caspase-3 activation in a dose dependent manner. Moreover, F3 fraction enhanced oxidative and nitrosative stress biomarkers and dissipated mitochondrial membrane potential in lung cancer cells along with significant depletion in cellular enzymatic and non-enzymatic antioxidants. Further, the apoptosis induced by F3 fraction was markedly prevented by the antioxidant N-acetylcysteine (NAC) suggesting the potential mechanism of oxidative stress. CONCLUSION: These findings suggest that F3 fraction could induce apoptosis in lung cancer cells through involvement of oxidative stress and mitochondrial dysfunction. Hence, these properties make F3 fraction a promising candidate for development of new anticancer agents.